Pengaruh Kualitas Pelayanan dan Kepercayaan Konsumen Terhadap Keputusan Pembelian - Meliana, Meliana; Sulistiono, Sulistiono; Setiawan, Budi (Jurnal Ilmiah Manajemen Kesatuan, 2013)
In today's era of globalization, rapid growth in the retail industry in Indonesia and is full of intense competition. Retail is one type of service companies that are closely related to the quality of service, so the researchers decided to examine the magnitude of the effect of service quality and consumer confidence in purchase decisions. Service quality is measured by three variables: the quality of interaction, the quality of the physical environment and quality of results. The method used in this study were: descriptive associative, while the data collection techniques conducted by distributing questionnaires. Questionnaire that will be deployed as many as 100 exemplar. To quantify this relationship, researchers used a method of path analysis with SPSS 17 for such tools. The results indicate that there is a fairly strong influence and significant relationship between service quality and consumer confidence as well as the influence of service quality and consumer confidence are also strong and significant impact on purchasing decisions. Keywords: Quality of Service, Consumer Confidence, Buying Decision.